Heller Myotomy: To Wrap or Not to Wrap?. Issue 6 (June 2018) - Brown, Jordan; Egger, Michael; Kehdy, Farid J.
Heller myotomy (HM) is widely recognized as the most effective treatment of achalasia. Although effective in improving dysphagia symptoms, HM is associated with reflux. Over a five-year period, 63 laparoscopic HM were performed. Patients underwent myotomy alone or HM plus reconstitution of the angle of His without any fundoplication, anterior, or posterior partial fundoplication. Two postoperative outcomes were examined: dysphagia and reflux. Twenty-two patients received no fundoplication (34.9%). Forty-one (65.1%) antireflux procedures were performed, including 21 reconstitutions of the angle of His (33.3%), nine (14.3%) anterior fundoplications, and 11 (17.5%) posterior fundoplications. All patients demonstrated preoperative dysphagia. Postoperative dysphagia was present in 23 of 63 (36.5%). Of these, 13 (56.5%) patients had an antireflux procedure, whereas 28 of 40 who had an antireflux procedure (70%) had no postoperative dysphagia (P = 0.28). Thirty-nine of 62 (62.9%) had symptomatic esophageal reflux preoperatively, and postoperative reflux was reported in 22 of 63 (34.9%). Reflux was present in 72.7 per cent of patients who had an antireflux procedure versus 61 per cent of those without the addition of an antireflux procedure (P = 0.415). However, HM independently improved reflux status regardless of whether an antireflux procedure was performed using the exact McNemar's test (P = 0.0014). Although the performance of an antireflux procedure did not appear to alter the reflux status after HM for achalasia, neither was it associated with postoperative dysphagia. More importantly, HM was independently associated with an improvement of reflux symptoms regardless of the type of antireflux procedure performed or whether one was used or not.